Effect of NAA concentrations on rooting of hardwood cuttings of Croton urucurana Baill., Tabernaemontana catharinensis A. DC. and Paullinia elegans Cambess. (FAVE Sección Ciencias Agrarias, 2021)
Effect of NAA concentrations on rooting of hardwood cuttings of Croton urucurana Baill., Tabernaemontana catharinensis A. DC. and Paullinia elegans Cambess. The objective of this work was to evaluate the rooting potential of “Sangre de Drago” (SD: Croton urucurana Baill.), “Horquetero” (TC: Tabernaemontana catharinensis A. DC.) and “Ojo de muñeca” (PE: Paullinia elegans Cambess.) cuttings by immersion in 1-Naphthaleneacetic acid (NAA). Two hundred cuttings without leaves per species were collected and immersed in 0, 1000, 2500 and 3500 ppm of NAA (for SD and TC) and 0, 500, 1000 and 2500 ppm of NAA for PE. At the end of the rooting period the following variables were registered on each cutting; the presence of roots, diameter at the base of the cutting (DAC) and rooting quality. Rooting probability was highest (0.76) for NAA than control (0.36) on SD cuttings. The rooting probability was very low on PE regardless of the NAA dose (0.13) but was directly proportional to the DAC. Root formation was not observed on TC, regardless of the NAA dose nor DAC. Rooting quality was unaffected by NAA dose but highly related to DAC in SD.
Keywords: naftalen acetic acid; indolbutiric acid; IBA; vegetative propagation; softwood cuttings; quick deep